On a family of Hopf algebras of dimension 72 - Andruskiewitsch, Nicolas (2012)
We investigate a family of Hopf algebras of dimension 72 whose coradical is isomorphic to the algebra of functions on S3. We determine the lattice of submodules of the so-called Verma modules and as a consequence we classify all simple modules. We show that these Hopf algebras are unimodular (as well as their duals) but not quasitriangular; also, they are cocycle deformations of each other.